2011
DOI: 10.3390/molecules161210387
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antibacterial Activities of Novel 2,5-Diphenylindolo[2,3-e] Pyrazolo[1',5':3",4"]pyrimido[2",1"-c] [1,2,4]triazines

Abstract: The formation of (E)-3-{2-(2,5-diphenylpyrazolo[1,5-c]pyrimidin-7-yl)hydrazono}indolin-2-ones 3 has been achieved by condensation of equimolar amounts of 7-hydrazino-2,5-diphenylpyrazolo[1,5-c]pyrimidine (1) and isatin (or isatin derivatives) 2at room temperature. The (E)-products could be isomerized into corresponding the (Z)-3 isomers. Reactions of the latter fused heterocyclic hydrazones towards different electro-philic reagents yielded the corresponding 3-substituted derivatives 4–7. Dehydrative cyclisatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Importance of pyrimidine in the medical field as therapeutic agents is well known [1][2][3][4]; also, it is used for the synthesis of a wide variety of bioactive azines [5][6][7][8]. Fused pyrimidines are among those azines which are found to exhibit many pharmacological activities such as antimicrobial [9,10] anti-inflammatory [11], anticancer [12], analgesic, anticonvulsant [13], antidiabetic [14], antioxidant [15], and antiviral [16] activity. In continuation of our efforts aimed to synthesize of fused azines derivatives [17,18]; we report herein about the utilization of thiopyrimidine derivative 1 for the construction of some novel annulated pyrimidines with expected biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Importance of pyrimidine in the medical field as therapeutic agents is well known [1][2][3][4]; also, it is used for the synthesis of a wide variety of bioactive azines [5][6][7][8]. Fused pyrimidines are among those azines which are found to exhibit many pharmacological activities such as antimicrobial [9,10] anti-inflammatory [11], anticancer [12], analgesic, anticonvulsant [13], antidiabetic [14], antioxidant [15], and antiviral [16] activity. In continuation of our efforts aimed to synthesize of fused azines derivatives [17,18]; we report herein about the utilization of thiopyrimidine derivative 1 for the construction of some novel annulated pyrimidines with expected biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrimidine is the structural unit of DNA and RNA, which plays a vital role in various existence progressions and the most abundant pyrimidine is uracil, cytosine and thymine. Besides these, anthracene moiety have also a remarkable range of biological activity mainly as antibacterial agents, antitumor, and antifungal compounds. Abd‐El‐Aziz et al reported that anthracene derivatives are also known for their [4+4] cycloaddition reactions as well as excimer generation and suggested the formation of the anthracene excimer with an emission at 510 nm …”
Section: Introductionmentioning
confidence: 99%
“…Pyrimidines continue to receive much attention in recent years due to their unique physical, chemical, and pharmacological applications as potential microbial growth inhibitors [1][2][3], photochemical probe agents [4], and biocidal agents [5]. A variety of nitrogen-bridged pyrimidines was reported to be used as multi-targeted small molecule inhibitors and resistance-modifying agents [6][7][8][9][10][11]. On the other hand, 1,2,4-triazines and their condensed hetrobicyclic ring systems have attracted considerable interest in recent years as anti-HIV [12], antifungal agents [13,14], molluscicidal agents [15], and antitumor agents [16].…”
Section: Introductionmentioning
confidence: 99%